Approbation of Combined Approach to Identification of Depressive Regions - AIMAGAMBETOV, Yerkara Balkarauly; ZHAILAUOV, Yerlan Berikovich (Journal of Advanced Research in Law and Economics, 2017)
In the research, the systematization of approaches to identification of depressive regions was carried out, and its main significant features were presented. The authors developed and approbated it based on the example of Karaganda region the combined approach to identification of depressive regions, based on the research of tempos of economical development and capacity of the region. The main purposes were defined regarding the rehabilitation of depressive regions depending on its potential.